The Art Of Social Work In Indonesia - Asmar Husein; Santoso Tri Raharjo; Eva Nuriyah Hidayat (Jurnal Ilmu Sosial Mamangan, 2021)
Social work is a unique relief profession as unique as individuals, groups and societies. Social relations as the main media in performing the art of social work practice. The art of social work practice is an expression of intuition results that creates creativity in dealing with social problems. In this century, it is necessary to show a brand new model of social work practice along with the emergence of contemporary social problems. So that in the Indonesian context, a unique character and characteristic are needed. This journal is a literature review from various sources that aims to present the new concept of the art of social work practice in Indonesia. So far, the science of social work has not been sufficient in dealing with social problems. Here is the urgency and connection between science and the art of social work practice. Thus, the relationship between the two cannot be separated. Because, basically, within the practice of social work lies an art.